2002
DOI: 10.4049/jimmunol.168.4.1823
|View full text |Cite
|
Sign up to set email alerts
|

Innate Direct Anticancer Effector Function of Human Immature Dendritic Cells. I. Involvement of an Apoptosis-Inducing Pathway

Abstract: Dendritic cells (DCs) mediate cross-priming of tumor-specific T cells by acquiring tumor Ags from dead cancer cells. The process of cross-priming would be most economical and efficient if DCs also induce death of cancer cells. In this study, we demonstrate that normal human in vitro generated immature DCs consistently and efficiently induce apoptosis in cancer cell lines, freshly isolated noncultured cancer cells, and normal proliferating endothelial cells, but not in most normal cells. In addition, in vivo ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
103
2
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 23 publications
6
103
2
3
Order By: Relevance
“…More recent studies, however, suggest that DC also play an important role, not only in the induction of tolerance, but also as cytotoxic anticancer cells. 19,20 Initial studies suggested these differing functional roles were carried out by distinct DC subsets such as the CD11c + and CD11c Ϫ blood DC identified in humans. 34 However, more recent data have demonstrated that these subsets do in fact have considerable functional plasticity 25,35,36 and their functional and clinical significance therefore remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies, however, suggest that DC also play an important role, not only in the induction of tolerance, but also as cytotoxic anticancer cells. 19,20 Initial studies suggested these differing functional roles were carried out by distinct DC subsets such as the CD11c + and CD11c Ϫ blood DC identified in humans. 34 However, more recent data have demonstrated that these subsets do in fact have considerable functional plasticity 25,35,36 and their functional and clinical significance therefore remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that immature but not mature DC are able to directly mediate anti-cancer activity. 19 The presence of elevated numbers of immature DC in PBSC grafts may therefore also have a direct effect on the malignant population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…72,73 Immature DCs have also been shown to kill freshly isolated tumors. [74][75][76] Although in vitro-derived immature DCs kill target cells very efficiently at low effector/target ratios via an apoptotic mechanism involving DNA fragmentation, mitochondrial dysfunction, and late membrane disruption, the level of cytotoxicity found in the freshly isolated, immature DCs remains low and questionable. 75 To note, while Chen's group 70 demonstrated that the tumor killing by immature DCs is mediated through direct cell-to-cell contact, Vujanovic's group 75 showed, using the same type of immature DCs, that the killing mechanism was mediated by both cell-to-cell contact and soluble mediators.…”
Section: Killer Dcsmentioning
confidence: 99%
“…(9) In addition, based on a series of publications, DC exert selective cytotoxic activity toward tumor cells, while demonstrating no cytotoxicity toward normal cells, such as dermal fibroblasts, epidermal melanocytes, mammary epithelial cells and T cell blasts. (10) We presumed that CBDC could act as effector cells to eliminate residual malignant cells after cord blood transplantation in hematologic malignancies. In direct support of this hypothesis, we obtained novel information that human CBDC are potent and promiscuous anticancer cytotoxic cells, capable of selectively killing hematological tumor cells through up-regulating the cytoplasmic TNF-α-related apoptosis-inducing ligand (TRAIL), without damaging the normal hematopoietic progenitor cells.…”
mentioning
confidence: 99%